ROTATIONAL ASSIGNMENT OF NEW BANDS IN THE NO , EXCITATION SPECTRUM IN THE SPECTRAL RANGE OF 15600 cm TO 15633 cm (Journal of Sciences, Islamic Republic of Iran)
Sub-Doppler excitation spectroscopy in a collimated cold supersonic beam of 5% NO seeded in argon has been performed with a spectral resolution down to 10 MHz for four vibronic bands within the perturbed B ?X A system of NO . The rotational temperature of about 15 K achieved by adiabatic cooling allows the separation of closely lying vibronic bands which overlap in absorption spectra taken at room temperature and which therefore could not be iden$- fied from the broad band excitation measurements